1987
DOI: 10.1111/j.1365-2044.1987.tb02987.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pregnancy on pulmonary nitrogen washout

Abstract: SummaryPre-oxygenation times were studied in 30fit pregnant women during the course of their pregnancy. The mothers were studied in the supine position with a left lateral tilt and breathing through a standard Magill system with an oxygenflopi. rate o f 8 litreslminute. Between 13-26 weeks gestation and 26-42 M>eek.r t h~ times needed to achieve un end-tidal nitrogen Of2Y0 1 4 w e I04 .second,s ( S D 30) and 80 seconds ( S D 20), respectiveL-y. A control group of young women of similar age and weight needed 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…This difference is predicted by increased ventilation of a relatively small functional residual capacity in pregnancy. This finding is in keeping with those of previous researchers [10–12]. We found that 2 min tidal breathing of 100% oxygen ensured > 95% complete pre‐oxygenation in full‐term pregnancy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This difference is predicted by increased ventilation of a relatively small functional residual capacity in pregnancy. This finding is in keeping with those of previous researchers [10–12]. We found that 2 min tidal breathing of 100% oxygen ensured > 95% complete pre‐oxygenation in full‐term pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Reduced functional residual capacity, coupled with increased minute ventilation, predicts more rapid pre‐oxygenation. There is a modest body of research in small numbers of subjects to support this [10–12]. However, research in pregnant patients suffers from ethical and practical constraints that have limited the work in this field.…”
mentioning
confidence: 99%
“…Максимальная преоксигенация у этих пациенток может быть достигнута быстрее за счет высокой альвеолярной вентиляции и сниженной ФОЕ. Однако во время апноэ беременные женщины склонны к более быстрому развитию десатурации оксигемоглобина из-за ограниченного объема кислорода в их сниженной ФОЕ в сочетании с повышенным потреблением кислорода (VО 2 ) [24].…”
Section: преоксигенация у пациентов с высоким рискомunclassified
“…1 environmental factors, geographical location, occupation, metabolic rate, hemoglobin concentration, functional residual capacity, state of the airway (closed vs. open), physiological shunt and dead space, obesity, pregnancy, critical illness, head injury, neuromuscular paralysis, etc. [3][4][5][6] India has a large diversity of population. This is influenced by different genetic pattern and geographical or regional factors.…”
Section: Introductionmentioning
confidence: 99%